Early Exploration of Employee Job Satisfaction Determinants - Wahdiniawati, Siti Annisa; Dera, Firman; P. Karo-karo, Alex; Pujiastuti, Endah; Rejeki, Sri (Indonesian Journal Economic Review (IJER), 2025)
This study aims to examine the impact of work stress and career development on job satisfaction at CV SAI Semarang. A quantitative research approach was employed for this study. The population consists of 39 employees at CV SAI Semarang. A non-probability sampling method was applied, utilizing a saturated sampling technique. The data analysis was conducted using descriptive analysis, classical assumption tests, coefficient of determination tests, and hypothesis testing, all processed with IBM SPSS software version 26. Research instruments included a questionnaire and an interview guide. The results revealed that work stress had a negative and significant effect on job satisfaction at CV SAI Semarang, while career development positively and significantly influenced job satisfaction. Furthermore, both work stress and career development, when considered together, had a positive and significant impact on job satisfaction at CV SAI Semarang.